3(8-2x)+5=17-2(1-x)

Simple and best practice solution for 3(8-2x)+5=17-2(1-x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(8-2x)+5=17-2(1-x) equation:



3(8-2x)+5=17-2(1-x)
We move all terms to the left:
3(8-2x)+5-(17-2(1-x))=0
We add all the numbers together, and all the variables
3(-2x+8)-(17-2(-1x+1))+5=0
We multiply parentheses
-6x-(17-2(-1x+1))+24+5=0
We calculate terms in parentheses: -(17-2(-1x+1)), so:
17-2(-1x+1)
determiningTheFunctionDomain -2(-1x+1)+17
We multiply parentheses
2x-2+17
We add all the numbers together, and all the variables
2x+15
Back to the equation:
-(2x+15)
We add all the numbers together, and all the variables
-6x-(2x+15)+29=0
We get rid of parentheses
-6x-2x-15+29=0
We add all the numbers together, and all the variables
-8x+14=0
We move all terms containing x to the left, all other terms to the right
-8x=-14
x=-14/-8
x=1+3/4

See similar equations:

| 700+k=1200 | | -9=z-23 | | (9x+4)(6x-4)=180 | | (8x+13x)*13x=(7+17)*17 | | (+27x^2-18x+12x-8)(3x-2)=180 | | 20j−18j=14 | | 15/6m+7=14 | | (9x+4)(3x-2)(3x-2)=180 | | (9x+4)(3x-2)=180 | | 4/7=m/28 | | F(x)=–x^2-7x-5 | | -14(d+3)=14 | | x=2/4(5x-4)=4x | | T=190+40w | | T=350+25w | | x^-3=118 | | 5x+19=45 | | r–17.1=−4.8* | | 900 =(n+2)180° | | 6(v+6)=72 | | 45=13x+19 | | 3x7-x=21 | | u/4-5=-1 | | 6(3k-4)=18k-24 | | 3p^2–40p+13=0 | | -14=1-5x | | -6(y+7)=-6 | | 4/15=1/4x | | 59=6x-5 | | 23x=9x | | 97-x=45 | | 19x+–9x=20 |

Equations solver categories